2016
DOI: 10.19082/2639
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of maternal-fetal attachment and health practices during pregnancy with neonatal outcomes

Abstract: IntroductionLow birth weight due to preterm delivery or intrauterine growth restriction (IUGR) is the strongest factor contributing to prenatal, neonatal, and postnatal mortality. Maternal–fetal attachment plays a significant role in maternal and fetal health. Health practices performed by the mother during pregnancy constitute one of the factors that may affect neonatal outcomes. The present study was conducted to identify the relationship between maternal–fetal attachment and health practices during pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 13 publications
(22 reference statements)
4
41
0
12
Order By: Relevance
“…There were also significant correlations between poor health before, during, and after pregnancy and inability to provide proper food and housing (38). In addition, previous studies have confirmed the correlation of low socioeconomic status with poor health and adverse pregnancy outcomes (39,40).…”
Section: Discussionmentioning
confidence: 66%
“…There were also significant correlations between poor health before, during, and after pregnancy and inability to provide proper food and housing (38). In addition, previous studies have confirmed the correlation of low socioeconomic status with poor health and adverse pregnancy outcomes (39,40).…”
Section: Discussionmentioning
confidence: 66%
“…Interventions aimed at reducing depressive symptoms that can occur during the gestational period and that can impact the psychological wellbeing of expectant parents and the development of a positive prenatal attachment should be implemented [155][156][157][158][159][160]. To enhance this bond takes on a main role, considering its further influence on postnatal depression (as most of the studies included in the current systematic review reported) [74,81,99,105,110,111], and on other important factors involved in the wellbeing of the both parents and the child [28,29,[32][33][34][35]37,38,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors underline that low maternal prenatal attachment is associated with low prenatal maternal fetus representations and self-care [25][26][27][28][29] and low postnatal attachment until 24 months postpartum [30][31][32][33][34][35][36][37][38][39]. Additionally, poor parental prenatal attachment has been connected to behavioral and conduct problems, lower cognitive development, and negative socioemotional regulations in early childhood [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the research indicates that prenatal attachment is negatively associated with harmful maternal behaviors and positively associated with behaviors that are more optimal during pregnancy. It is then not surprising that prenatal attachment has also been associated with negative neonatal outcomes such as low birth weight [ 33 , 43 ].…”
Section: Introductionmentioning
confidence: 99%